Evaluation of the training program of the community medicine interns based on the Kirkpatrick model - Bahar Moarrab; Lida Jarahi; Seyed Masoud Hosseini; Ali Emadzadeh; Roya Moallem; Mojtaba Mousavi Bazaz (Future of Medical Education Journal)
Background: Evaluation of the educational program plays a crucial role in improving educational quality. This study aimed to evaluate the educational programs of community medicine interns based on the Kirkpatrick model.Method: This descriptive-analytical research was conducted in the Community Medicine Department of the Medical Faculty of the Mashhad University of Medical Sciences from 2015 to 2018. All medical students who were community medicine interns in health centers in Mashhad during four academic years were included in the study by census method (n = 568). The educational program was evaluated on three levels: reaction, learning, and behavior. P < 0.05 was considered significant in all statistical tests.Results: The study found an overall satisfaction score of 87.02%, with a slight decline over the four academic years. However, the overall satisfaction remained relatively high. The mean learning score in all three categories progressively improved across the years (p<0.05). The total Kirkpatrick learning score also increased significantly (p< 0.001). The behavioral change scores showed a fluctuating overall upward trend over the four academic years, indicating the positive impact of the training program on interns' behavior. The improvement in behavioral change was statistically significant (F = 6.31, p = 0.00).Conclusion: The investigation of the Community Medicine internship program utilizing the Kirkpatrick model offers a thorough comprehension of its efficacy in improving interns' satisfaction, learning of skills, and behavior.